IMPROVING YOUNG LEARNERS’ PRONUNCIATION SKILL THROUGH SONGS - Dian Palupi; Evi T Prasetyaningsih; Sayyidah Bilandari (ETERNAL (English Teaching Journal), 2022)
One of the essential language aspects of English acquisition is pronunciation. Teaching pronunciation starts from younger age help the learners recognize the way to pronounce accurately. This article is based on classroom action research aiming at improving the young students’ pronunciation through songs. The subjects of the research were 23 young learners, the students of grade IV. There were two cycles in this classroom action research in which the researchers used songs as the intervention. The students were introduced to some English songs related to their materials and were asked to practice singing in the class. A test was administered to know the current students’ pronunciation skill before the intervention (pre-test), and also a post-test at the end of every cycle to find the difference before and after they were taught with songs. The mean score of the pre-test showed that the students’ pronunciation skill was in the range of “fair”. After that, the mean score of post-tests 1 and post- test 2 showed that the student’s pronunciation skill was improved to the range of “good” and “very good”. Moreover, during the observation, the researchers also found that the students got more motivated in learning English by the use of songs. Thus, it can be concluded that the students’ pronunciation skill is improved through the use of songs in the learning process.